Rhein promotes the proliferation of keratinocytes by targeting oestrogen receptors for skin ulcer treatment - Ning Xu; Yuanran Chen; Dongjie Guo; Yu Deng; Wanjun Guo; Xin Liu; Yi Wang; Hanzhi Lu; Aijun Liu; Jianyong Zhu; Fulun Li (BMC Complementary Medicine and Therapies, 2022)
Abstract Background The Sheng-ji Hua-yu (SJHY) formula is a quite effective Traditional Chinese Medicines (TCM) in the treatment of delayed diabetic wounds. Previous research has shown that the SJHY formula has significant anti-inflammatory and wound-healing effects, but the precise mechanism remains unknown. The purpose of this study was to evaluate the effects of rhein, a compound extracted from SJHY formula, in keratinocytes and to investigate the underlying mechanisms. Methods Microscale thermophoresis (MST) technology was used to confirm that rhein binds directly to oestrogen receptors (ERs). Rhein was then used to treat keratinocytes in vitro. Cell cycle and proliferation analysis, Real-time polymerase chain reaction (RT-PCR) and Western-blot were conducted. Results Rhein increased the proportion of cells in the S phase of the cell cycle and promoted keratinocyte proliferation. ICI 182,780, an ER inhibitor, was also used to treat keratinocytes. The expression of c-myc mRNA and protein induced by rhein was antagonized by ICI 182,780, indicating that this induction is ER dependent. Intervention with ICI 182,780 had no effect on the upregulation of FosB and JunD, indicating that activator protein 1 (AP-1) members (FosB and JunD) are involved in rhein-induced c-myc mRNA and protein expression but does not require the ER. Conclusion The present study found that rhein stimulates keratinocyte proliferation by activating the oestrogen signalling pathway via the oestrogen receptor, which induces the expression of c-myc in collaboration with FosB and JunD, thereby accelerating the process of re-epithelialization.